Pemikiran Politik K.H. Moenawar Chalil (1908-1961) - Aqimuddin, Jafar Tahmid; Fajriudin, Fajriudin; Marliana, Dina (Historia Madania: Jurnal Ilmu Sejarah, 2021)
K.H. Moenawar Chalil is an important figure who is almost forgotten in Indonesian history. He is one of the Indonesian scholars who existed in his time. He has several famous works that he has written since becoming a member of the Sarekat Islam in 1925 at the age of 17 years. Some of his works have been published in articles, newspapers, and the biggest one is in a book that is until now widely known, The Complete Date of the Prophet Muhammad. It turned out that he not only published books on the history of the Prophet Muhammad, but other books such as religious themes, and also politics. This research aims to reconstruct the political thought of K.H. Meonawar Chalil in Indonesia which is contained in his work, both from articles, newspapers and books. The study used four stages, namely Heuritics, Criticism, Interpretation and Historiography.